Proteomic Analyses Of Excretory Secretory Proteins (Esp) And Membrane Proteins Of Entamoeba Histolytica HM1:IMSS - Ujang, Jorim (2018)
Entamoeba histolytica is a protozoan parasite that causes amoebiasis. Infection of this parasite may lead to amoebic dysentery and amoebic liver abscess, which is fatal if left untreated. Until now, understanding of the pathogenesis of amoebiasis is limited. Hence, in this study, proteomic analyses were performed on the excretory-secretory (ES) and the membrane sub-proteomes of E. histolytica trophozoites. A total of 209 ES proteins were identified in which 191 and 97 proteins were detected by LC–ESI–MS/MS and LC–MALDI–TOF/TOF, respectively. Of the 209 proteins, 79 were identified by both mass-spectrometry systems, while 112 and 18 proteins were detected exclusively by LC–ESI–MS/MS and LC–MALDI–TOF/TOF respectively. Subsequently, the secretome prediction analyses were performed whereby 8 and 31 out of 209 total proteins were identified as classically and non-classically secreted proteins, respectively. Functional annotation classification showed that the largest ES protein class, which is 23%, is the oxidoreductase. The second part of this study involved the comparison of three membrane protein extraction methods: two commercial kits (ProteoExtract® from Calbiochem and ProteoPrep® from Sigma), and a conventional laboratory method. The results showed that the ProteoExtract® kit and the conventional method extracted higher protein yields compared to the ProteoPrep® kit. The combined data from LC-MALDI-TOF/TOF and LC-ESI-MS/MS identified 490, 492, and 587 proteins extracted using the ProteoExtract®, ProteoPrep®, and conventional methods,respectively. In-silico analysis predicted 109 (22%), 237 (48%) and 182 (31%) membrane proteins from the ProteoExtract®, ProteoPrep® and conventional method extracts, respectively. Furthermore, the identification of the cytosolic and membrane protein fractions showed that the ProteoPrep® extraction kit was the most selective and specific for the extraction of the membrane proteins. In conclusion, the results revealed 39 and 249 E. histolytica ES and membrane proteins, respectively. Furthermore, this study confirmed that the use of two types of mass spectrometers enhances proteome coverage. The data generated has increased the understanding on the types of proteins that are excreted-secreted by E. histolytica and also the proteins that reside at the parasite’s membrane. The identified proteins will be useful for further studies in understanding the pathogenesis of amoebiasis and the roles the proteins play in the host-parasite interactions.